AND SHE’S LIKE IT ’S TERRIBLE, LIKE: SPOKEN DISCOURSE, GRAMMAR AND CORPUS ANALYSIS - Adolphs, Svenja; Carter, Ronald (International Journal of English Studies, 2003)
This paper argues for the imporiance of teaching frequent words in English and for using computer corpora as a guide to decisions over which words to teach. The article contains a case study of a word which is frequent in both written and spoken English but more frequent in spoken English. The use of a spoken corpus raises complex questions conceming the teaching of grammar, especially frequent words in a ’discourse grammar’ and these are discussed in relation to evidence of contexts of use, the needs of the learner and the use of authentic language data in the foreign language classroom.